2017
DOI: 10.1111/mcn.12502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a smartphone nutrition and physical activity application to provide lifestyle advice to pregnant women: The SNAPP randomised trial

Abstract: Our objective was to evaluate the impact of a smartphone application as an adjunct to face-toface consultations in facilitating dietary and physical activity change among pregnant women.This multicentre, nested randomised trial involved pregnant women with a body mass index and at 36 weeks of pregnancy −1.16 (CI [−4.60, 2.28]). There was no significant additional benefit from the provision of the smartphone application in improving HEI score (p = .452). Although all women improved dietary quality across pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 49 publications
(66 reference statements)
2
78
1
Order By: Relevance
“…A recent meta-analysis demonstrated the increasing prevalence of mHealth-supported randomized controlled trials for weight management in pregnancy (17). Despite a greater publication of studies using mHealth tools to promote maternal behaviors, few have focused on diet and physical activity specifically, and among those that have, mixed results have been reported (18,19). Freely available smartphone apps are generally low quality and contain limited behavior change techniques and pregnancy-specific nutrition information; thus, it has been suggested that they are not an appropriate resource for pregnant women (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated the increasing prevalence of mHealth-supported randomized controlled trials for weight management in pregnancy (17). Despite a greater publication of studies using mHealth tools to promote maternal behaviors, few have focused on diet and physical activity specifically, and among those that have, mixed results have been reported (18,19). Freely available smartphone apps are generally low quality and contain limited behavior change techniques and pregnancy-specific nutrition information; thus, it has been suggested that they are not an appropriate resource for pregnant women (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the main characteristics of the included studies and study populations. The studies were conducted in Australia ( n = 6) [ 39 , 41 , 43 , 51 , 53 , 54 ], the USA ( n = 5) [ 38 , 45 , 47 , 48 , 49 ], and across Europe ( n = 6), including the UK ( n = 3) [ 38 , 40 , 52 ], Norway [ 44 ], Finland ( n = 1) [ 50 ], and Greece ( n = 1) [ 46 ]. The five studies from the USA all included a majority of Hispanic participants.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, most participants were enrolled in the studies in their first or second trimester, often between 14- and 20-weeks of gestation. Three studies recruited participants from pre-existing RCTs on antenatal nutrition [ 41 ], influenza vaccination [ 49 ], or mother and infant nutrition and probiotics [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This claim was proven based on the ANOVA test obtained from the nutrition apps for the depression levels and BMI p-value which was more than 0.05. Dodd et al [52] and Olson et al [53] claimed that low use of mHealth apps affected the effectiveness of the output. However, in this study, we found that other than the frequency of mHealth apps use, the types of app also affected the effectiveness of the app's intervention in person's life.…”
Section: Discussionmentioning
confidence: 99%